Parotid oncocytoma in Birt-Hogg-Dubé syndrome: a new pitfall in 18F-Fluorodeoxyglucose Emission Tomography/Computed Tomography imaging study - Subha, Sethu Thakachy; Nordin, Abdul Jalil; Mohtarrudin, Norhafizah; Ahmad Saad, Fathinul Fikri (Universiti Putra Malaysia Press, 2016)
Oncocytomas are rare head and neck neoplasms that occur most commonly in the parotid salivary gland. Birt-Hogg-Dube syndrome is a rare inherited genodermatosis manifested by a group of cutaneous lesions, in association with several renal and lung pathology, parotid oncocytoma, thyroid and colonic tumours. Here we report on the case of a patient who presented with parotid oncocytoma in association with skin lesions, multinodular goitre and uterine leiomyoma. This array of lesions suggested the possibility of Birt-Hogg-DubÃ© syndrome. 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (18F FDG PET/CT) was used to evaluate head and neck malignancies, including salivary gland tumours. In this report, we highlight a case of bilateral parotid oncocytoma with suspected BirtHogg-DubÃ© syndrome that showed increased FDG uptake in a PET-CT study. This marked FDG avidity in a benign parotid oncocytoma, adding to the list of common pitfalls related to the parotid glands during a FDG PET-CT study.